Experimental harvest reveals the importance of territoriality in limiting the breeding population of Svalbard rock ptarmigan - Pedersen, Åshild Ønvik; Soininen, Eeva M; Unander, Sigmund; Willebrand, Maria Hörnell; Fuglei, E. (European Journal of Wildlife Research, 2013)
The Svalbard rock ptarmigan (Lagopus muta hyperborea) is an endemic subspecies of rock ptarmigan inhabiting the high Arctic archipelagos of Svalbard and Franz Josefs Land. This ptarmigan species exists at low population densities, with little interannual variations in population numbers, and limited habitat for breeding with less than 5 % of the land area in Svalbard constituting medium to high quality breeding habitat. Unander and Steen (1985) hypothesized, based on a descriptive study, that territories sufficiently attractive for breeding could be a limiting factor of the Svalbard rock ptarmigan population. Here, we use experimental data from a 3-year removal experiment (1984–1986) to test their hypothesis by comparing breeding density, demography (sex and age ratios) and body mass of birds between experimental removal plots and control locations. We found evidence of surplus birds by showing that both sexes of Svalbard rock ptarmigan replaced quickly in vacant territories after removal of the resident birds, and that breeding densities were similar for the experimental and control populations. Replaced males in the breeding population weighed less than males in the initial breeding population and tended to be younger. Experimental harvest during the preceding spring had no effect on male body mass, population sex ratio or the proportion of juvenile males in the pre-breeding population the following spring. The documented surplus of male and female Svalbard rock ptarmigan and a lack of impact on breeding densities from removal of birds leave a proportion available for harvest.